Pengaruh Pertumbuhan Ekonomi, Upah Minimum, Pendidikan Dan Pengangguran terhadap Kemiskinan di Provinsi Bali - I Gusti Agung Ngurah Bagus Wiadnyana; Sis Hadiyati (J-MAS (Jurnal Manajemen dan Sains), 2023)
This study aims to find out whether there is an effect of economic growth, minimum wage, education and unemployment on poverty in the province. The type of research is quantitative, the variables in this study are poverty as a dependent variable and economic growth, provincial minimum wage, education, unemployment, as an independent variable.Â  The sample collection technique in this study used annual data that was measured in a time series from 2007-2021. Which means that the data used is 14 years. In this study the population of Economic Growth, Provincial Minimum Wage, Education, Unemployment and Poverty in Bali Province. The regression analysis used in this study is a multiple linear regression model. The results of the following research economic growth have not been able to become indicators that affect poverty significantly because the impact of economic growth can only be felt directly on rich people, and cannot be directly felt by poor people so that it cannot have a significant effect. minimum based on the cost of living required in a province, in this study UMP was not able to significantly affect Poverty. Education is influential in overcoming poverty. Unemployment in Bali cannot significantly affect poverty.